Capital account liberalization and its effects on economic growth and financial instability: the exante orthodox models were wrong - Garcia Angelico, Diego; Contendo de Oliveira, Giuliano (Brazilian Journal of Political Economy, 2020)
The financial crises in emerging economies during the 1990s and 2000s propelled academia and multilateral institutions to investigate whether the promised benefits of capital account liberalization were being delivered or not. In the course of empirical studies on the subject, many ex ante theoretical assumptions on financial globalization were demystified, and previously unknown risks and dysfunctions began to be evidenced. This article analyzes the main empirical studies on the effects of financial globalization published in the last two decades and shows that the main conventional assumptions that were built to theoretically base the capital account liberalization processes that occurred in the 1980s and 1990s were wrong. JEL Classification: F3; F4; F6.